2019
DOI: 10.1155/2019/1964107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IOP Measurement by Goldmann Applanation Tonometer, ICare Rebound Tonometer, and Tono-Pen in Keratoconus Patients after MyoRing Implantation

Abstract: Purpose. To evaluate the different IOP readings by Goldmann applanation tonometer (GAT), ICare rebound tonometer, and Tono-Pen in keratoconus patients after MyoRing implantation. To assess the influence of central corneal thickness (CCT) and thinnest corneal location (TCL) on IOP measurements by different tonometers. Setting. Prospective observational study was conducted in two private centers in Egypt from February 2015 to November 2016. Methods. Seventeen eyes of 10 patients suffering from keratoconus and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…This study was in perfect agreement with our study. 13 Rateb M et al 14 in their study concluded that there was no significant correlation between the IOP measurements done using different tonometers, this was contrary to our present study finding, which showed a significant positive correlation between the measurements…”
Section: Discussioncontrasting
confidence: 99%
“…This study was in perfect agreement with our study. 13 Rateb M et al 14 in their study concluded that there was no significant correlation between the IOP measurements done using different tonometers, this was contrary to our present study finding, which showed a significant positive correlation between the measurements…”
Section: Discussioncontrasting
confidence: 99%
“…Our study showed a positive correlation between IOP readings taken by both air puff and GAT tonometers, and CCT, but both were statistically insignificant (p-value 0.190, 0.058 respectively). These results were consistent with those of Rateb et al's 16 study, where there was no significant correlation between CCT and any of the IOP measurements taken by GAT, Icare rebound tonometer, and Tono-Pen in KCN patients after MyoRing implantation.…”
Section: Discussionsupporting
confidence: 92%
“…However, it did not find a significant difference between GAT/Tono-Pen readings, where the p-value was 0.554, while Bland-Altman analysis showed a reasonable agreement between each pair of the tonometers. 16 In our study, there was a significant difference between the three tonometers readings (p-value <0.001) using ANOVA measure. By using the correlation coefficient, no agreement was found between any pair of them.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…31 KC is most common in adolescents and young adults and occurs in both boys/men and girls/women. 11 In the present study, we selected SP-A1 as a biomechanical factor to analyze its correlations with DIOP1 and DIOP2 and adjusted the age and CCT. The differences between DIOP1 and DIOP2 were correlated with SP-A1 in all 3 groups after adjustment for CCT and age.…”
Section: Discussionmentioning
confidence: 99%